1992
DOI: 10.1530/acta.0.1270267
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone degradation by opossum kidney cells via receptor-mediated endocytosis and lysosomal hydrolysis

Abstract: The mechanisms involved in parathyroid hormone (PTH) degradation by proximal renal tubule cells were studied using an opossum kidney cell line possessing PTH receptors as an in vitro model system. One hour incubation of 5 nmol/l human (h) PTH-(1-84) with intact opossum kidney cells (4.0\m=x\ 106 cells) resulted in about 70% degradation and disappearance of hPTH-(1-84) from the medium, as determined by a two-site immunoradiometric assay. Preincubation with 100 nmol/l h[Nle8, Nle18, Tyr34]PTH-(1-34)amide for 6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In opossum kidney cells most PTH was subjected to endocytosis and lysosomal degradation, whereas a minor fraction of the hormone was metabolized by extracellular chymotrypsin-like endopeptidases (10,11,27). It has been suggested that in opossum kidney cells the PTH/PTHrP receptor is responsible for the endocytic uptake of the hormone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In opossum kidney cells most PTH was subjected to endocytosis and lysosomal degradation, whereas a minor fraction of the hormone was metabolized by extracellular chymotrypsin-like endopeptidases (10,11,27). It has been suggested that in opossum kidney cells the PTH/PTHrP receptor is responsible for the endocytic uptake of the hormone.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, cellular uptake and degradation of PTH was demonstrated directly in cultured proximal tubular cells. In these cells, the PTH/PTHrP receptor was suggested to mediate the uptake and degradation of the hormone (10,11). Whether this receptor is also responsible for systemic clearance of PTH or whether alternative uptake mechanisms exist in vivo remained unclear.…”
mentioning
confidence: 99%
“…AI-ternatively, OK cells are suitable for studying PTH degradation at the basolateral surface specifically, because the effect of luminal microvillar hydrolytic activities is negligible. Indeed, our study showed that C-terminus or mid-portion of PTH, hPTH-(39-84) or hPTH-(39-68), which are known to be hydrolyzed solely at the luminal microvillar membranes in animal studies [1,6], were scarcely degraded by the monolayer cultures" of OK cells [26]. In contrast, about 70 % of hPTH-(1-84) added in the media was readily hydrolyzed by these cells via a receptor-mediated endocytosis and subsequent lysosomal hydrolysis at the basolateral surfaces.…”
Section: Cellular Mechanisms Of Pth Degradation At the Basolateral Sumentioning
confidence: 77%